(untitled) (International Journal of Engineering and Computer Science, 2015)
The disposal and treatment of hazardous waste is very costly affairs for the environment, it has been a dormant issue. The new millennium brings challenges for the civil and environmental engineers and opportunities for research on the utilization of the solid waste and by-products and basic properties of concrete and its materials. The recycling of waste after burnt in incinerator attracts an increasing interest worldwide due to the high environmental impact of the cement and concrete industries.